Design and construction of a Power Meter to optimize usage of the Electric Power (2014)
In this article, we present Electric Power Meter, a device that allows us to measure the energy consumption per electrical circuit even for each device at home. Detailed knowledge of the consumption of each device will allow us to identify which devices are those that increase the cost of our bill. Likewise, our device will help to identify when one of them is not working properly. In this prototype, we use a co-design methodology hardware-software. Our design is based on open platforms, both hardware and software. Preliminary results show that our meter can monitor a three-phase load or three single-phase three loads with an average error less than 5% when it estimates the instantaneous power. © 2014 IEEE.